BOOK REVIEW: Koenraad Verboven, Christian Laes (eds.), “Work, Labour, and Professions in the Roman World”, Leiden – Boston, Brill, 2016, 353 p., ISBN 9789004331655, Hardback - PÁZSINT, Annamária-Izabella (Studia Universitatis Babeș-Bolyai Historia, 2018)
The present volume is part of the series Impact of Empire: Roman Empire, c. 200 BC – AD 476, being the second book resulted from the research programme Factors of Production in the Roman World. More precisely, it represents the proceedings of a conference bearing the same name, which was held between the 30th of May and the 1st of June 2013, in Ghent. The central focus is, as the title points out, the role played by the human resources in the Roman economy, and the sections of the conference were built accordingly, around four main topics: a) labour relations (the introduction and the following five articles), b) organization, specialization, skills and learning (articles 7 and 12), c) professional organizations (articles 9-11), and d) identities and ideologies (articles 8 and 13); this structure having been changed, in some aspects, in the printed version.